Impact of sulfur and nitrogen fertilization on seed composition of soybean - Rahman, Aadil A.; Brooks, Keren; Conley, Shawn P.; Gaska, John M.; Irby, Trent; Knott, Carrie; Lee, Chad; Lindsey, Laura E.; Mourtzinis, Spyros; Naeve, Seth; Ross, W. Jeremy; Singh, Maninder P.; et al. (Frontiers in Sustainable Food Systems, 2025)
U.S. soybean (Glycine max [L.] Merr) is an important source of nutrition worldwide, with a 2022 export value of 34.3 billion. Nitrogen (N) and sulfur (S) fertilizer inputs can influence nutritional quality of seed due to their roles in amino acid biosynthesis. However, the role of N and S fertilizers needs to be further evaluated due to high nutrient demands from increased crop yields. This study examines the impact of N and S fertilizer applications on soybean composition in diverse environments across the U.S. Two S sources, ammonium sulfate (AMS) and gypsum (CaSO4), were tested at three rates (11, 22, and 33 kg S/ha). Three additional treatments included urea applied at nitrogen (N) rates of 10, 20, and 29 kg N/ha, equivalent to the N rates supplied by AMS, to assess the impact of N in AMS. All fertilizers were manually broadcast at planting, and a control treatment with no fertilizer was included. Data were collected from 40 sites in 9 states over 2019 and 2020. The effect of the 10 fertilizer treatments on soybean seed protein, oil, and sulfur-containing amino acid content was assessed. ANOVAs were performed with linear fixed effects models separately for each year of the study (2019 and 2020). Results showed that fertilizer rates had a significant effect on protein, oil, cysteine and methionine content which varied by growing environment. Our findings suggest that S and N fertilization, particularly with high rates of AMS or medium rates of gypsum, can significantly enhance cysteine and methionine content in soybeans across various environments, improving the nutritional value for human and animal consumption.